Role of circ_0002590 in Neuroinflammation Via the miR-1184/NLRP1 Axis in Painful Diabetic Neuropathy - Liu, Qiao; Chen, Mengdie; Cai, Xinxiao; Feng, Ping (Experimental and Clinical Endocrinology & Diabetes, 2025)
Painful diabetic neuropathy (PDN), a severe microvascular complication of diabetes, is closely associated with neuroinflammation. This study aimed to investigate the mechanism of circ_0002590 in neuroinflammation associated with PDN.The Schwann cells (HEI193) were treated with high glucose (HG, 150 mM) to simulate the diabetic microenvironment. Circ_0002590 expression was silenced using siRNA interference technology and was determined by quantitative real-time reverse transcription polymerase chain reaction. Inflammatory cytokines levels were measured by enzyme-linked immunosorbent assay. The cell counting kit-8 assay was utilized to determine cellular viability. Bioinformatic predictions (TargetScan 8.0 and circRNA Interactome databases) combined with dual-luciferase reporter gene assays and RNA pull-down assays were employed to validate the correlation linking circ_0002590 and miR-1184, as well as between miR-1184 and Nod-like receptor pyrin domain-containing 1 (NLRP1). Rescue assays were performed to confirm the function of the circ_0002590/miR-1184/NLRP1 competing endogenous RNA (ceRNA) network in PDN-associated neuroinflammation.HG treatment significantly upregulated circ_0002590 expression in HEI193 cells, promoted inflammatory cytokine release, and reduced cell viability. These effects were reversed after circ_0002590 silencing. Circ_0002590 directly interacted with miR-1184 and suppressed miR-1184 expression. miR-1184 targeted and inhibited NLRP1 expression. miR-1184 inhibition or NLRP1 overexpression reversed the anti-inflammatory effects mediated by circ_0002590 silencing.HG activates the inflammatory response in Schwann cells by inducing circ_0002590 expression, which competitively binds with miR-1184 and thereby alleviates its inhibitory effect on NLRP1.
Keywords: Painful diabetic neuropathy; NLRP1; circ_0002590; miR-1184; Neuroinflammation